Historias de vida de meninas com experiência pregressa nas ruas: perspectivas do processo de inclusão social - OLIVEIRA, Normalene Sena de (2006)
In this inquiry, we sought for answers to some questions about social adjustment process for children and adolescents in street situation, especially for female adolescents that had found alternatives for a better quality of life out of the treets. The main objective was to analyze the meaning for social adjustment; to identify the institutional pedagogic programs in the social adjustment process; and to analyze the meaning of the social adjustment and the consequences to female adolescents that lived in street situation. The method has qualitative approach by Oral Live History principles. The data was collect by semi structured interview and participant observation with eight adolescents from 16 to 24 years old, with previous history of life in streets, and analyzed by content analysis thematic modality background. The results was organized and presented through the following categories: 1) coming to street; 2) living in street; 3) life beyond the street. In accordance with the subjects, the social adjustment process occurred in pregnancy consequence. However, the awakening of new live perspectives occurred due significant persons in a specific sheltering institution and the pedagogical actions there developed that accompany, motivate and articulate the values of these persons in the whole process. Therefore, by the oral history of life it was possible to identify the subject course of life, its social adjustment in the recuperation process and the Public Health Nursing possibilities for caring in this process of social adjustment